The European and international currency problem - MAGNIFICO, G. (PSL Quarterly Review, 2013)
Many argue that the crisis of the international monetary order founded at Bretton Woods is acting as a catalyst in the process of European monetary unification. Others, however, argue that the mounting disorder into which the Bretton Woods order has drifted is hampering that process and that, sooner or later, it will wreck the whole E.C. construction. The present article assess the international currency problem with regards to European integration, showing that it is probable that each of the arguments put forth have valid points. The author argues that the frictions produced by the process of reform have put a strain on international economic and monetary cooperation just when it needed to be strengthened in order to meet new challenges. Moreover, the repeated efforts to restore the monocentric reserve-currency system and the all round obligation to maintain fixed exchange rages are misdirected endeavours. JEL: E42, F36, F33